Tinjauan Literatur Pangan lokal di Indonesia - Sadeli, Agriani Hermita; Qanti, Sara Ratna; Syamsiyah, Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Local food plays a role in enhancing economic, social, and environmental sustainability. However, maximizing the utilization of local food faces various challenges. This study aims to identify publication trends and synthesize knowledge in the context of local food in Indonesia.     This study employed the PRISMA diagram for a systematic literature review and Vosviewer for bibliometric analysis. The data used in this research consisted of articles on local food in Indonesia from the Scopus database. Publications on local food in Indonesia have increased from 1994 to the present. The journal with the most scientific articles is the Journal of Biodiversity. Based on bibliometric analysis, words related to local food in Indonesia can be clustered into 5 clusters. Future research in the context of local food in Indonesia can be linked to small and medium enterprises, farmers, nutritional status, health, and traditional food.